Research Review: Model Permainan Tradisional dalam Meningkatkan Kebugaran Fisik dan Karakter Siswa - Ajito, Timoteus; Sudatha, I Gde Wawan; Suartama, I Kadek; Santosa, Made Hery (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Traditional games are regional games in Indonesia that contain cultural values to train behavior and sharpen the cognitive and motor skills of individuals. However, along with the development of the times, traditional games are increasingly eroded by technological advancements and social changes, so they are becoming less commonly played by children today. This study aims to provide an overview of research trends on traditional games through a Systematic Literature Review of articles published in Scopus-indexed journals from 2020 to 2022. The analysis method used in this study is bibliometric, with the assistance of Publish or Perish (PoP) software utilizing the Google Scholar database and VOSviewer for visual data mapping. The bibliometric analysis process is carried out in five stages: (1) determining search keywords, (2) collecting initial data, (3) filtering results, (4) compiling initial statistics, and (5) analyzing data. Based on the keywords used, 86 relevant articles were identified. The results of the study show that traditional games are effective in improving physical fitness and shaping students' character